Study on the Development of Interregional Synergistic Construction (Taking the China-Belarus Industrial Park and the International Land Port of Gansu as Examples) - Т. Qu (Управленческие науки, 2024)
The year 2023 marks the 10th anniversary of the initiation of the «One Belt and One Road» initiative. Belarus, as one of the countries along the One Belt and One Road, is actively responding to the initiative’s call and participating in its joint implementation. The author creatively establishes a connection and conducts a profound analysis of the China- Belarus Industrial Park and the International Land Port of Gansu (Lanzhou). The article assesses the present status and development progress of the two projects, identifying pertinent issues and proposing solutions through a methodical approach that combines theoretical analysis with practical application. A theoretical framework for these two projects is presented, aiding in surmounting challenges and charting the future trajectory of collaboration. The study’s objective is to introduce novel developmental concepts for Park administrators and policymakers, while also pinpointing fresh avenues for growth within the Park development of both countries, to contribute to economic advancement more effectively.